Development of High Yielding and Early Maturing Cotton Variety Cyto-178 With Better Adaptation to Climatic Condition of Punjab - Ashraf, Farzana; Hayat, Khezir; Imran, Hafiz Muhammad; Akbar, Muhammad; Muhammad, Noor; Hameed, Asifa; Aslam, Rashida; Ahmad, Adeel; Mian, Muhammad Azam; Adnan, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
To meet the increasing demand for cotton and improve fibre quality, the development of high-yielding, early-maturing, and disease-resistant cultivars remains essential for sustainable cotton production in Pakistan. Objective: This study aimed to develop and evaluate a new cotton cultivar, Bt. Cyto-178, for its agronomic performance, fibre quality, and adaptability under diverse agroecological conditions in Pakistan. Methods: Bt. Cyto-178 was developed at the Cytogenetic Section of the Central Cotton Research Institute (CCRI), Multan, Pakistan, from a cross between (Neelum 121 × Exotic material) × SL-365/1 (Cyto-124) during the 2003–04 cotton season. Selection was conducted from the F₂ to F₈ generations based on phenotypic traits, yield potential, and fibre quality. The cultivar was tested for 12 years in CCRI research plots, farmers’ fields, and multi-location National Coordinated Varietal Trials (NCVT) across Punjab, Sindh, and other cotton-growing regions. Results: Bt. Cyto-178 consistently outperformed existing commercial cultivars in both preliminary and advanced yield trials. It ranked 10th in national yield performance during the 2014–15 season and demonstrated superior traits including early maturity, high yield, and resistance to major diseases. The cultivar is especially well-suited for the agroecological conditions of Punjab. Conclusion: Bt. Cyto-178 is a robust, early-maturing, and high-yielding cotton cultivar with enhanced fibre quality and disease resistance. Approved by the Punjab Seed Council in 2020, it is recommended for general cultivation across cotton-growing regions of Pakistan.